Standardization of traditionally designed neutraceutical - Padmaja, Deepa; Kannappan, Nagappan (International Current Pharmaceutical Journal, 2012)
Plants are the rich source of a variety of chemicals with nutritive and therapeutic properties. The pharmacological activities of allopathic drugs are now decreased before the herbal potency. Now most of the pharmaceutical companies are focusing in this area. The Indian pharmaceutical industry is definitely looking forward to a tremendous herbal marketing. The traditionally designed neutraceutical is an Ayurvedic herbal formulation; consist of Brahmi, Tulsi, and other ingredients in powder form. This neutraceutical is proved for its antibacterial and antioxidant activity. Standardization of the traditionally designed neutraceutical is compared with the marketed product. The uses of medicinal plants are increased in developing nations. Nations like India, is a rich source of Ayurvedic plants. Government of India is also promoting the member states to formulate national policies on traditional medicine. Quality assurance is an integral part of traditional medicine. A comprehensive specification must be developed for each herbal drug preparation based on recent scientific data. DOI: http://dx.doi.org/10.3329/icpj.v1i9.11621 International Current Pharmaceutical Journal 2012, 1(9): 288-293